Doing a dam better : the Lao People's Democratic Republic and the story of Lao Nam Theun 2 - Porter, Ian C.; Shivakumar, Jayasankar, 1938- (Directions in Development., 2011)
In the wake of an acrimonious debate on big dams, the World Bank brokered a global agreement on financing as well as on the sharing of the rewards and risks of the controversial Nam Theun 2 hydroelectric project in Lao PDR. Through this process, it prepared the project for the country and the country for the project. This book describes how careful management, effective communications, and technical expertise helped to reach consensus and nurtured private-public partnerships, engaged stakeholders, strengthened the country's development framework and poverty reduction efforts, and addressed the.